The job quality of young higher education graduates in Portugal: Contractual arrangements & wage differentials - Suleman, F.; Figueiredo, M. C. T. (LEED 2017 WORKSHOP, 2017)
This article explores the wage differentials among young graduates engaged in different contractual arrangements. We use linked employer-employee data – “Quadros de Pessoal”, for 2012, to examine the quality of jobs of young graduates in Portugal. We estimate the impact of flexibility (stability) and full (part) working time on wages. More specifically, this study examines the impact of four types of contractual arrangements, notably Standard, Underemployed, Insecure, and Non-Standard. Empirical analysis adopts the treatment effect model to deal with imprecise and inconsistent estimates arising from the OLS earnings model. It is assumed that graduates themselves can select, or at least accept, the contractual arrangement; therefore we use a treatment-outcome model for multinomial choice of contractual arrangements. The results of the impact of four types of contract suggest that stability benefits graduates whether they have full or part contract. The findings show that graduates’ labour market is segmented in Portugal. Furthermore, labour market ranks graduates on the basis of field of education. Graduates from health, mathematic and statistics, and transport services earn higher wages.